The rules, practice, and jurisprudence of international courts and tribunals - Giorgetti, Chiara (Leiden : BRILL, 2012)
This book examines existing international disputes resolution institutions of both general and specific subject-matter jurisdiction. Uniquely, it assesses both procedural rules and essential case-law, making it relevant for both academics and practitioners in international law.
B. Full Protection and Securityc. Other Legal Standards; 3. Expropriation; D. Conclusion; Chapter Four The International Tribunal for the Law of the Sea; A. Overview; 1. Essential Information; 2. Jurisdiction; 3. Procedural Overview; a. Instituting Proceedings; b. Languages; c. Preliminary Proceedings and Objections; d. Provisional Measures; e. Proceedings; f. Permission to Intervene; g. Amicus Curiae; h. Decision; i. Expenses; j. Financial Assistance; B. Review of the Case Law; 1. Judgments on Provisional Measures; 2. Judgments on Prompt Release of Vessels and Crews; 3. Pending Cases.
4. Discontinued Cases.
Print version record.
eBooks on EBSCOhost
Keywords: Civil procedure; International courts; Law; Tribunaux internationaux; LAW -- International; Civil procedure; International courts; Law